Establish the DC Motor Programmable System Control for Training. - Le , Thế Vinh; Duong , Công Hiệp; Nguyen , Minh Quân; Bui , Xuân Vinh; Le , Thị Ngọc Hà (Journal of Technical Education Science, 2008)
The programmable system control DC motor has been investigated and established by means of both simulation and experiment. It aims to give a medium for training and to improve professional skills for the studenst. The current work presents the results of the study on this system by simulation method using Electronics Workbench software. The characteristics and behavior of D/A Converter, Power-Amplifier and DC motor also discuss